Transformasi Identitas Religius dan Spiritualitas dalam Era Sekularisasi: Perspektif Sosiologi Agama - Nesia Mu’asyara; Merhan Merhan; Ria Ulfa; M. Fikri Arfandi; Ajeng Yurike; M. Okan Fattah; Imas Imas; Vindy Agela C.A; Tarisa Dewi Anggina (Concept: Journal of Social Humanities and Education, 2024)
This research aims to understand how secularization affects changes in religious identity and individual spirituality, as well as religious practices in modern society, through the perspective of the sociology of religion. Using a qualitative approach and literature review methods, this study presents the research process chronologically, keeping the research objectives focused, proving the problem statement, and discussing the relationship between theory, research questions, study focus, and its application in the context of specific societies. The findings show that secularization often leads to a separation between religion and daily life, resulting in a reinterpretation of religious and spiritual values. The sociology of religion explains how individuals and communities adjust their religious practices to remain relevant in an increasingly secular environment. This research also outlines various theoretical perspectives on secularization and its impact on religious identity and spirituality, as well as how religious practices are adapted in modern society. Through this study, it is hoped that a deep understanding of the dynamics between religiosity, spirituality, and secularization will be obtained, as well as their impact on religious identity and religious practices in modern society. The research emphasizes the importance of religion remaining relevant in the modern era and how religion can adapt to changing times to maintain balance and morality in an increasingly secular society.